STUDI KARAKTERISTIK PELAKU PERJALANAN KOMUTER KOTA YOGYAKARTA YANG BERDOMISILI DI DAERAH SLEMAN DAN BANTUL - , TEGUH PRADANA PUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Problems of congestion in the City of Yogyakarta in general occurs at peak hours in the morning and evening. At those times, there is a same movement in the City of Yogyakarta, so that causing congestion in the road sections. Some of the perpetrators of these movements is the traveling commuters, the journey is done repeatedly in the day-to-day work. In general, the traveling commuters coming from suburban areas such as Bantul and Sleman Regency. The research was conducted in the City of Yogyakarta in particular on the commuting travel. The data needed are the characteristics of the respondents in choosing a mode of transportation to travel. In practice, a survey conducted by distributing questionnaires and interview forms directly to the respondents. Then the data obtained from the survey results were analyzed with multiple regression. The survey results revealed that out of 161 respondent, there are 120 commuters using motorcycle mode for commuting travel, which means that there are dependency to use motorcycle mode (captive user). Regarding to the factors influencing travel mode choice, travel time becomes the most important factor that affects the transportation mode choice of the traveling commuter. Transportation Modes that have the most effective travel time is motorcycle, this is evidenced by 83% respondents that use motorcycle have a travel time of less than 30 minutes. Beside travel time, ownership of motorcycle become another factor that make respondents chose motorcycle as their choice. For respondents that chose public transportation as their choice, factor that significantly influence them is ownership of motorcycle. Thatâs because, generally only respondents that donât own motorcycle chose to travel by public transportation. Whereas for respondents who chose private car as their vehicle factors thatâs influence them are income, ownership of car and gender.